2023
DOI: 10.1101/2023.03.03.23286787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrast-Enhanced Magnetic Resonance Imaging Based T1-Mapping and Extracellular Volume Fractions are Associated with Peripheral Artery Disease

Abstract: Background: Extracellular volume fraction (ECV), measured with contrast-enhanced magnetic resonance imaging (CE-MRI), has been utilized to study myocardial fibrosis but its role in peripheral artery disease (PAD) remains unknown. We hypothesized that T1-mapping and ECV differ between PAD patients and matched-controls. Methods and Results: A total of 37 individuals (18 PAD, 19 controls) underwent 3.0T CE-MRI at the mid-calf. T1-mapping was done before and after gadolinium contrast with a motion corrected Modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This study adds to the growing body of evidence that T1 mapping and ECV quantification are providing reproducible measures of tissue characterization including but not limited to diffuse fibrosis and other pathophysiological changes in response to inflammation, the hallmark of atherosclerosis and PAD [15,16,25].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This study adds to the growing body of evidence that T1 mapping and ECV quantification are providing reproducible measures of tissue characterization including but not limited to diffuse fibrosis and other pathophysiological changes in response to inflammation, the hallmark of atherosclerosis and PAD [15,16,25].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies reported the high reproducibility of myocardial T1 mapping [14,15]. However, the role of T1 mapping and ECV values remains poorly understood in PAD [16]. For the present work, we studied the role of the T1 mapping and ECV quantification of the skeletal calf muscles in PAD patients and controls.…”
Section: Introductionmentioning
confidence: 94%